Experimental investigation of combustion characteristics of a CH4/O2 premixed flame: Effect of swirl intensity on flame structure, flame stability, and emissions - Minsung Choi; Keun Won Choi; Do Won Kang; Hafiz Ali Muhammad; Young Duk Lee (Case Studies in Thermal Engineering, 2024)
An experimental work was carried out to investigate the effects of swirl intensity on the flame structure and emission characteristics in a swirl-stabilized premixed oxy-fuel flame for application to oxy-fuel gas turbines. To analyze the flame structure, instantaneous photographs and OH radical chemiluminescence images were collected over various conditions. In addition, the gas emissions (NOx, CO, and O2) have also been measured and analyzed. The results show that the flame structure and the longitudinal distribution of CO concentration inside the combustor are strongly affected by the swirl intensity. At a higher swirl intensity, the flame shapes are short and flat; consequently, the CO dissipates rapidly downstream. In contrast, at a lower swirl intensity, flames are long-drawn and the CO remains longer in the downstream region of the combustor. Among the various swirl number, considered in this study, 0.8 is determined as an optimal value for ensuring flame stability and controlling emissions.